Sabay tayo a proposed toolkit to promote simultaneous planting among farmers in Sitio St. Joseph, Cabiao, Nueva Ecija - Sarmiento, Allana Marie O.L.; Dans, Sandra Michelle (Quezon City College of Fine Arts, University of the Philippines Diliman, 2024)
Rice is the most important crop in the Philippine agricultural sector playing a significant role in the food security, economy, employment, and overall sustainability It is globally recognized as an essential food and a major source of income for millions of Filipinos. Within the Philippines, Nueva Ecija, recognized as the nation's primary rice-producing province and referred to as the rice granary of the Philippines with 318,284 hectares of land area. Despite its prominent role, the province still faces challenges such as extreme weather events, diseases, and pest infestations, leading to crop damage and low yields. Farmers do not also have access to information and resources that would help them prevent the effects on rice production. An alternative approach is to support them through farmer's association or other collaborative initiatives aimed at improving farmers' well-being by enhancing productivity and increasing income. The study's purpose is to determine the various factors affecting the rice production of farmers in Sitio St. Joseph, Cabiao, Nueva Ecija, with the goal of developing a visual communication intervention in response.

During the needs finding, the study revealed a problem within a rice production, where farmers lack coordination on planting schedules, shifting to individualistic farming practices and isolated decision-making. With this, the study aims to answer the question: "How might we increase the coordination among the farmers from Sitio St. Joseph, Cabiao, Nueva Ecija on the simultaneous rice planting.

The "Sabay Tayo" is a toolkit designed to promote a collaborative environment and provide farmers with information about the significance and benefits of simultaneous rice planting. It also functions as practical and legible which can help them develop plans, coordinate with farm neighbors, and schedule dates for planting and harvesting.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 55-57
Keywords: Farming; Farming -- Rice .; Rice -- Planting